A Bibliometric Analysis of Global Research Trends on Food Security Policy: Insights for Sustainable Governance - Zulkifli Hasan; Hadi Daryanto; Suwarno Suwarno (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Food security is a strategic global issue that involves policy, governance, and sustainable development dimensions. This study examines global research trends on food security policy using a bibliometric approach based on 125 scientific publications published between 2020 and 2025. Utilizing the Scopus database and analytical tools such as RStudio, VOSviewer, and Publish or Perish, the study maps the most influential sources, leading authors, contributing countries, and the most frequently discussed topics. The findings show that